The importance of the consultation process in order to implement public policies. Public consultation on enhanced cooperation against vaccine-preventable diseases - Rus, Mihaela; Tasențe, Tănase; Tănase, Georgiana (Technium Social Sciences Journal, 2022)
Between 20-25 November 2020, we applied a questionnaire on public consultation on enhanced cooperation against vaccine-preventable diseases, on a sample format of 130 responses. The objectives of the research were to measure the social perception of citizens about public vaccination policies during the Covid-19 pandemic. Also, this case study aims to identify the factors that influence the vaccination program, ways and initiators of communication on the safety, efficacy and effectiveness of vaccination, both for citizens and for medical specialties. In addition, another objective is to identify the credibility of vaccination campaigns and their effective evaluation. Moreover, this study aims to find out people’s perception of how each state should adapt to internal needs (relative to European public policies), but also the opinion of respondents about the responsibility for information and ways to document them with scientific and convincing arguments, concluding how well a public health policy could be managed if there is adequate consultation.